IMPLEMENTASI MANAJEMEN MUTU DI SD SWASTA BANI ADAM AS - Nasrul Syakur Chan; Rusli Kembaren; Toni Julham; Wirda Hasanah Hasanah; Yayi Setia Ningrum (Jurnal Sabilarrasyad, 2020)
Organizing Resources in Improving Education Quality at SD Bani Adam AS is carried out with a detailed process of all work that must be carried out by each individual in achieving organizational goals, the division of workload into activities that can be carried out by each individual and the development of work mechanisms so that there is coordination of the work of the members of the organization into an integrated and harmonious union. The implementation of the Education Quality Improvement Plan in Bani Adam AS Elementary School has not yet fully followed the stages of the implementation of general guidelines for implementation, because the concepts and objectives of the policy have not been fully understood by the policy actors as a result of the implementation of policy socialization which is somewhat less than optimal. Apart from that, it is also caused by the lack of empowerment of school principals, teachers or educators, school committees and not giving full authority and freedom to the principal as the main policy actors and also the teachers who implement the policies, as well as the lack of courage and good reactivity carried out by the school principal or teacher or educator at SD Bani Adam AS.